Pentafluoroethylsilicic Acids. Issue 50 (9th November 2016) - Schwarze, Nico; Steinhauer, Simon; Neumann, Beate; Stammler, Hans‐Georg; Hoge, Berthold
Abstract: Pure anhydrous hexafluorosilicic acid (H2 [SiF6 ]) is a still elusive species, although its existence in aqueous solutions is well documented. Desiccation inevitably leads to decomposition to form tetrafluorosilane and hydrogen fluoride. An oxonium hexafluorosilicate turned out to not be stable at room temperature. Partial substitution of the fluorine atoms with strong electron‐withdrawing perfluoroalkyl groups results in substantial stabilization of the corresponding fluorosilicic acids. Mono‐ and bis(pentafluoroethyl)‐substituted fluorosilicic acids were prepared through conversion of the respective halosilanes (Si(C2 F5 ) n X4− n, with X=Cl, Br) with aqueous HF, and were obtained as colorless solids. They can be stored at room temperature for several months without decomposition, and thus are the first examples of stable fluorosilicic acids. Abstract : Pure anhydrous hexafluorosilicic acid (H2 [SiF6 ]) is still an elusive species, although its existence in aqueous solutions is well documented. Substitution of the fluorine atoms with pentafluoroethyl groups results in substantial stabilization of the corresponding fluorosilicic acids. Mono‐ and bis(pentafluoroethyl)‐substituted fluorosilicic acids were prepared by treating the respective halosilanes with aqueous HF.